KONDISI KEUANGAN WAJIB PAJAK PEMODERASI PENGARUH SANKSI PERPAJAKAN, KESADARAN WAJIB PAJAK PADA KEPATUHAN WAJIB PAJAK - Perdana Yasa, I Putu Risky; Jati, I Ketut (E-Jurnal Akuntansi, 2017)
This study aims to determine the effect of the financial condition the taxpayer as a moderating influence tax penalties and awareness of the taxpayer for the tax compliance of motor vehicles. The theory used in this research is theory of Compliance. The population in this study are all active CLA taxpayers registered at the Office of Joint SAMSAT Denpasar. The samples used in this study were 100 respondents calculated by Slovin method of the accsidental sampling method. The data collection was conducted using non-participant observation and questionnaires. Data analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that the awareness of tax penalties and taxpayers significant positive effect on motor vehicle tax compliance. Besides moderating variables, namely the taxpayer's financial condition can also moderate the effect of tax penalties and awareness of the taxpayers on tax compliance vehicles.
Keywords: Tax Penalties, Taxpayer Awareness, The Financial Condition of Taxpayer, Taxpayer Compliance